2017
DOI: 10.1016/j.bbagen.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for small molecule glycomimetics in the protection against lipid-induced endothelial dysfunction: Involvement of Akt/eNOS and Nrf2/ARE signaling

Abstract: Background: Glycomimetics are a diverse array of saccharide-inspired compounds, designed to mimic the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 56 publications
4
45
0
Order By: Relevance
“…An explanation for this declined expression of Nrf2 could be the chronic and surplus production of ROS. This notion is supported by our recent findings where we demonstrated downregulation of the Nrf2/ARE/HO-1 pathway in different conditions with excessive production of ROS [34, 48, 7274]. Furthermore, the anti-inflammatory effect of C. molmol resin extract could be attributed, at least in part, to the activation of Nrf2.…”
Section: Discussionsupporting
confidence: 78%
“…An explanation for this declined expression of Nrf2 could be the chronic and surplus production of ROS. This notion is supported by our recent findings where we demonstrated downregulation of the Nrf2/ARE/HO-1 pathway in different conditions with excessive production of ROS [34, 48, 7274]. Furthermore, the anti-inflammatory effect of C. molmol resin extract could be attributed, at least in part, to the activation of Nrf2.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, it could also be exploited to counteract the anti-angiogenic effect of aging on ECFCs. Parallel work conducted on an endothelial model of lipid-induced oxidative stress showed that the glycomimetic C3 was able to recruit the Nrf2/ARE and Akt/eNOS signaling pathways, thereby exerting a cytoprotective effect and rescuing NO release [ 175 ]. Similarly, pre-treatment of diabetic ECFCs with adiponectin rescued in vitro migration and neovessel formation in a mouse model of hindlimb ischemia under both normo- and hyperglycemic conditions [ 176 ].…”
Section: Manipulation Of Pro-angiogenic Signaling Pathways To Imprmentioning
confidence: 99%
“…We then applied the methodology to the original medicinal chemistry challenge, the sodium salt of glycomimetic C3 (10). 8 High conversion and an isolated yield of 76% on a 500 mg scale was achieved. The methodology was applied to the Fmocprotected amino acid, serine, resulting in excellent yields (95% under normal conditions) and 90% at a non-denaturing temperature (11) both using 4.0 eq.…”
mentioning
confidence: 94%
“…1 Sulfate groups on glycosaminoglycans (GAGs) such as heparin, heparan sulfate and chondroitin sulfate, facilitate molecular interactions and protein ligand binding at the cellular surface, 2 an area of interest in drug discovery. 3 Heparin (an anticoagulant), 4 avibactam s (a b-lactamase inhibitor), 5 sotradecol (a treatment for varicose veins), 6 the sulfate metabolite of paracetamol (an analgesic), 7 and the glycomimetic C3 (used to study atherosclerosis), 8 contain organosulfate motifs (Fig. 1).…”
mentioning
confidence: 99%